Empathy Mediates the Effects of Age and Sex on Altruistic Moral Decision Making - Rosen, Jan B.; Brand, Matthias; Kalbe, Elke (Frontiers in Behavioral Neuroscience, 2016)
Moral decision making involves affective and cognitive functions like emotional empathy, reasoning and cognitive empathy/theory of mind (ToM), which are discussed to be subject to age-related alterations. Additionally, sex differences in moral decision making have been reported. However, age-related changes in moral decision making from early to late adulthood and their relation to sex and neuropsychological functions have not been studied yet. One hundred ninety seven participants (122 female), aged 19 to 86 years, were tested with a moral decision making task comprising forced choice “everyday life” situations in which an altruistic option that favors a socially accepted alternative had to be considered against an egoistic option that favors personal benefit over social interests. The percentage of altruistic decisions was analyzed. A structural equation model (SEM) was calculated to test the hypothesis whether age and sex predict altruistic moral decision, and whether relevant neuropsychological domains mediate these hypothesized relationships. A significant relationship between age and moral decision making was found indicating more frequent altruistic decisions with increasing age. Furthermore, women decided more altruistically than men. The SEM showed that both age and sex are significant predictors of altruistic moral decision making, mediated by emotional empathy but not by reasoning. No cognitive empathy and ToM scores were correlated to age and moral decision-making at the same time and thus were not included in the SEM. Our data suggest that increasing age and female sex have an effect on altruistic moral decisions, but that this effect is fully mediated by emotional empathy. The fact that changes of moral decision making with age are mediated by emotional empathy can be interpreted in the light of the so-called “positivity effect” and increasing avoidance of negative affect in aging. The mediated sex effect might represent both biological aspects and socialized sex roles for higher emotional empathy leading to more altruistic decisions.